Molecular Detection of Tropical Theileriosis in Cattle of Chhattisgarh Plains, India - Rawte, Sonu Ram; Bagh, Kashee Ram; Bisen, Savita; Pal, Susanta; Raj , Lourde (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Theileriosis, a tick borne protozoan disease, drastically affects the productivity of bovine with massive economic repercussion. The current investigation was conducted to determine the molecular prevalence of T. annulata employing cytochrome b gene based PCR assay. Investigation was conducted on 150 blood samples of cattle obtained from three districts, viz. Rajnandgaon (50), Balod (50) and Kabirdham (50) of Chhattisgarh state. Initially microscopic examinations of smears were done followed by PCR analysis of DNA samples. The overall prevalence of tropical theileriosis in plain region of Chhattisgarh was found to be 27.3% (41/150) and 54.0% (81/150) by microscopy and PCR assay, respectively. Among districts, highest prevalence 32% and 60% was recorded in Kabirdham followed by 22% and 54% at Balod and 28% and 50% at Rajnandgaon, by microscopy and PCR assay, respectively. Observations showed that, more number of infected animals were from unorganized farm (62.6%) than organized farm (45%). Present study revealed crossbred cattle more susceptible to T. annulata infection than indigenous animals.